ROLE OF AHARA AS A PRIME ETIOLOGICAL FACTOR IN THE MANIFESTATION OF DISEASE - Raina, *Triveni; Kishor, Brij; Saini, Swapnil; Sharma, Dalip (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda considers Ahara (food) as one of the three supporting pillars. Food has been given prime importance since Vedic Period. It is considered as Brahma in Upanishad. Acharaya Kashyapa gives it the name Mahabhaisajya. This is responsible for the growth, development and enhancement of Ojas. The body as well as diseases; both psychological and lifestyle disorders like Heart disease, Obesity, Diabetes, Hypertension and Cancer being the major health problems are formed by food, wholesome and unwholesome food are responsible for happiness and misery respectively. The disease can be cured without any medication by just following wholesome regimen, whereas even hundreds of medicines cannot be cure a disease in absence of wholesome regimen. Ahara rasa which is formed from ingested diet nourished not only our body but also nourished mind and sensory organs. Ayurveda describes that Deha is made up of Ahara and the Vyadhi also. According to Laulimbaraja Pathya is the secret of healthiness likewise Apathya is the root cause of all diseases. Ayurvedic Acharayas describes importance of Ahara differently especially in Brihatrayee, a special chapter has been described for Annapana Vidhi. The principle of dietetics and nutrition in Ayurvedic system of medicine include different classes of Ahara i.e. eating and drinking items, principle of Pathyapathya (wholesome and unwholesome diet), discipline of eating (Ashta Ahara Vidhi Visheshayatan, Dvadasha Asana Vidhi etc.), Viruddha Ahara (incompatible diet). Ashta Ahara Vidhi Visheshayatan includes eight discipline of eating and Dvadasha Asana Vidhi includes the twelve discipline of eating as described by Acharya Charaka and Sushruta respectively and is very important in daily life for promotion of positive health.